POTENSI EKSTRAK TEH HIJAU (CAMELLIA SINENSIS) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA TIKUS GALUR WISTAR: SYSTEMATIC REVIEW - Filda Nisrina Fajrin (2022)
Diabetes mellitus (DM) is a group of metabolic disorders characterized by hyperglycemia due to insulin secretion disorders, insulin action disorders or due to both. The number of DM sufferers that continues to increase every year makes the prevalence of DM in Indonesia reach 6.2% of the total population in 2019. Green tea (Camellia sinensis) can be a supportive therapy in lowering blood glucose levels by various mechanisms. This study aims to determine the potential of green tea extract (Camellia sinesis) to reduce blood glucose levels in Wistar rats with diabetes mellitus model. Methods: Systematic review based on PRISMA-P 2020 with a literature search strategy using Google Scholar, PubMed, Science Direct, and Scopus databases. Literature quality was assessed using the JBI Critical Appraisal Checklist which produced 12 comprehensive potential literatures based on selection with inclusion and exclusion criteria. Results: Analysis of 12 journals found that there were 11 studies that showed a significant decrease in blood glucose levels after administration of green tea extract (Camellia sinensis). Conclusion: Green tea extract (Camellia sinensis) has the potential to reduce blood glucose levels in Wistar strain rats with diabetes mellitus model. The mechanism underlying the antihyperglycemic effect is proven to be due to the protective and antidiabetic effects of the compounds contained in green tea extract, especially the flavonoid group, namely catechins. The minimum dose of green tea extract observed to cause an antihyperglycemic effect in experimental animals was 40 mg/kgBW